2022
DOI: 10.3390/su14148850
|View full text |Cite
|
Sign up to set email alerts
|

Disintegration Resistance of Steep-Rocky-Slope Wall-Hanging Soil Based on High-Performance Ester Materials

Abstract: Ecological restoration is difficult on the steep rocky slopes (SRS) in rainy areas in South China that experience severe soil erosion. The disintegration resistance of steep-rocky-slope wall-hanging soil (SRSWS) is a crucial topic in the field of new ecological restoration. The formation of a transient saturated zone of wall-hanging soil (WS) under high-intensity rainfall can easily lead to soil disintegration. The subsequent rain erosion can cause the loss of growth substrate required for early plants, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…A description of the development of the utilized red-bed ecological membrane can be found in another paper by our team. The polymer adhesive used was a type of strong water-based nano-adhesive, and the polymer water-retaining material used was a type of water-retaining material with good water absorption and retention performance; both materials will eventually degrade into CO 2 and H 2 O [14,17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A description of the development of the utilized red-bed ecological membrane can be found in another paper by our team. The polymer adhesive used was a type of strong water-based nano-adhesive, and the polymer water-retaining material used was a type of water-retaining material with good water absorption and retention performance; both materials will eventually degrade into CO 2 and H 2 O [14,17].…”
Section: Methodsmentioning
confidence: 99%
“…Bhattarai [11] developed three different types of biodegradable erosion control blankets, all of which can reduce soil erosion to varying degrees. The optimization of planting substrates also plays a crucial role in the slope protection performance of ecological aggregation, where the ratio of planting substrate materials can affect the ecological performance of the ecological aggregation [12][13][14]. Faucette [15] added various fertilizers to planting blankets to enhance the plant growth rate of the blankets and found that using compost and a planting blanket can effectively reduce the soil erosion of the slope and enhance its erosion resistance [16].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer adhesive material is often used in dispersions prepared with water, and it has a high viscosity and soil consolidation. The material is also degradable, with a degradation cycle of 24 months (the long-term resistance will be researched next) under natural conditions, and will be degraded into CO 2 and H 2 O without generating any hazardous substances [28][29][30].…”
Section: Methodsmentioning
confidence: 99%